Case Report: Post-surgical Guillain-Barré syndrome as a rare differential diagnosis of flaccid paralysis of the lower extremities in an infant after cardiac surgery - Gross, Maximilian; Berger, Rafal; Neunhoeffer, Felix; Nordmeyer, Johannes; Bevot, Andrea (Frontiers in Pediatrics, 2025)
IntroductionGuillain-Barré syndrome (GBS) is an important cause of flaccid paralysis in children and is mainly associated with antecedent infections. Surgery as an additional trigger for GBS is a well-documented phenomenon in adults, but is significantly less reported in pediatric patients. This case report describes an infant with post-surgical GBS following cardiac surgery, highlighting the diagnostic challenges and differential diagnoses of post-surgical GBS in the pediatric intensive care setting.Case descriptionA former extremely preterm infant with congenital cytomegalovirus (CMV) infection underwent a second surgery for re-coarctation of the aorta with aortic arch hypoplasia at the chronological age of six months. While requiring extracorporeal membrane oxygenation postoperatively, the girl presented with flaccid paralysis of the lower extremities. Magnetic resonance imaging of the brain, spine, and nerve conduction studies demonstrated findings consistent with acute motor-sensory axonal neuropathy-type GBS. She was treated with intravenous immune globulin and ganciclovir due to CMV reactivation (plasma 14,000 copies/ml). Gradual neurological improvement was noted over the following months, while persistent motor deficits remained, suggesting potential disease transition into chronic inflammatory demyelinating polyneuropathy.ConclusionsThis case report emphasizes the importance of considering post-surgical GBS in critically ill children with postoperative paralysis. Recognition may be delayed due to variable initial presentations and accompanying factors such as sedation and extracorporeal life support.